Scan-find-scan-model: discrete site-targeted suppressor design strategy for amyloid-beta - Bhagavatula, Hasathi; Sarkar, Archishman; Santra, Binit; Das, Atanu (ACS Chemical Neuroscience, 2022)
Alzheimer's disease is undoubtedly the most well-studied ranks at the top in terms of getting attention from the scientific community for structural property-based characterization. Even after decades of extensive research, there is existing volatility in terms of understanding and hence the effective tackling procedures against the disease that arises due to the lack of knowledge of both specific targetand site-specific drugs. Here, we develop a multidimensional approach based on the characterization of the common static-dynamic-thermodynamic trait of the monomeric protein, which efficiently identifies a small target sequence that contains an inherent tendency to misfold and consequently aggregate. The robustness of the identification of the target sequence comes with an abundance of a priori knowledge about the length and sequence of the target and hence guides toward effective designing of the target-specific drug with a very low probability of bottleneck and failure. Based on the target sequence information, we further identified a specific mutant that showed the maximum potential to act as a destabilizer of the monomeric protein as well as enormous success as an aggregation suppressor. We eventually tested the drug efficacy by estimating the extent of modulation of binding affinity existing within the fibrillar form of the A beta protein due to a single-point mutation and hence provided a proof of concept of the entire protocol.
Keywords: configurational misfoldability; drug developability; inherent frustration; potential aggregability; sequence-based mutability; target specificity

Solvation structure and dynamics of a small ion in an organic electrolyte - Kore, Shivshankar; Sahoo, Rudhi Ranjan; Santra, Binit; Sarkar, Archishman; Chowdhury, Tubai; Deshmukh, Samadhan H.; Hazarika, Sulagna; Chatterjee, Srijan; Bagchi, Sayan (Journal of Photochemistry and Photobiology A-Chemistry, 2023)
Organic carbonates are commonly used as electrolytes in commercial lithium-ion batteries. A detailed interpretation of the solvation structure and dynamics of the electrolyte around ions is necessary to understand the charge/discharge process in batteries. This work combines infrared absorption spectroscopy with quantum chemical calculations and molecular dynamics simulations to decipher the solvation structure of propylene carbonate, a cyclic carbonate, around the dissolved thiocyanate ion. Two dimensional infrared spectroscopy and polarization-selective pump probe spectroscopies have been utilized to extract the timescales of solvent fluctuation and the solute reorientational dynamics. The similarity in the slow timescales for the solute and the solvent dynamics signifies that similar processes control both dynamics.